Bimbingan Teknis Tata Kelola Pemerintahan Desa dalam Menyusun Laporan Keuangan dan Pelayanan Masyarakat Desa Sungai Liput Dusun Buluh Betong Kecamatan Kejuruan Muda Kabupaten Aceh Tamiang - Mangkuwinata, Sonny M. Ikhsan; Haryani, Haryani; Mangkuwinata, Denny Sumantri; Aselia, Putri; Fitriana, Cut Nadia; Al Kausar, Riski (LPPM Umuslim, 2025)
Village government organizations are currently required to have good governance management in preparing financial reports and services, and this is very important to implement in protecting the needs of village communities. Therefore, the ability of village officials to manage governance, especially in providing services to the community, is a necessity. This knowledge and ability are very much needed to support the performance of public services at the Sungai Liput Village Office, Buluh Betong Hamlet, Kejuruan Muda District in Aceh Tamiang. With good service governance and the ability of caring village government human resources, transparent and accountable governance will be created as well as easy, fast, and accurate services so that the community can be comfortable in interacting. Therefore, this Technical Guidance activity aims to improve scientific understanding and skills, especially regarding governance and service management for local Village Apparatus.